2003
DOI: 10.1128/jb.185.11.3288-3296.2003
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Aggregation-Promoting Factor to Maintenance of Cell Shape in Lactobacillus gasseri 4B2

Abstract: Aggregation-promoting factor (APF) was originally described as a protein involved in the conjugation and autoaggregation of Lactobacillus gasseri 4B2, whose corresponding apf gene was cloned and sequenced. In this report, we identified and sequenced an additional apf gene located in the region upstream of the previously published one. Inactivation of both apf genes was unsuccessful, indicating that APF function may be essential for the cell. Overproduction of APF proteins caused drastic alteration in the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 35 publications
2
67
1
1
Order By: Relevance
“…This indicated that E. coli produces the recombinant Cpf in a correctly folded conformation. Furthermore, all attempts to inactivate cpf and heterologously express cpf in L. reuteri or L. sakei failed (data not shown), indicating that Cpf may play an important role in cell surface composition, as recently demonstrated for Apf of L. gasseri (19).…”
Section: Characterizationmentioning
confidence: 90%
See 1 more Smart Citation
“…This indicated that E. coli produces the recombinant Cpf in a correctly folded conformation. Furthermore, all attempts to inactivate cpf and heterologously express cpf in L. reuteri or L. sakei failed (data not shown), indicating that Cpf may play an important role in cell surface composition, as recently demonstrated for Apf of L. gasseri (19).…”
Section: Characterizationmentioning
confidence: 90%
“…The Apf proteins have recently been described as novel surface proteins (48). In L. gasseri the Apf is involved in the maintenance of the cell shape (19). On the other hand, little data are available about the coaggregation of lactobacilli and its mechanism.…”
mentioning
confidence: 99%
“…farciminis 3699 involves carbohydrate-lectin interactions and/or proteinaceous components present on the surface. Autoaggregation is a known property of some Lactobacillus isolates (Collado et al, 2007(Collado et al, , 2008 and allows the formation of biofilm in the gastrointestinal tract which contributes, as a physico-chemical barrier, to the preservation of the intestinal wall, along with the stimulation of the immune system (Jankovic et al, 2003;Castagliuolo et al, 2005;Voltan et al, 2007;Turpin et al, 2010), and to protection against colonization by pathogenic bacteria (Collado et al, 2007(Collado et al, , 2008. Furthermore, bacteria with a high autoaggregation potential will more easily colonize the intestinal and urogenital tracts (Boris et al, 1998;Cesena et al, 2001;Collado et al, 2005Collado et al, , 2007Collado et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Four L. plantarum proteins contain a C-terminal domain of approximately 60 amino acids characterized by conserved tryptophan and tyrosine residues. Experimental studies in Lactobacillus gasseri and Lactobacillus johnsonii suggest that proteins containing this domain are involved in aggregation and/or maintenance of cell shape (Jankovic et al, 2003;Ventura et al, 2002).…”
Section: Novel Domainsmentioning
confidence: 99%